Short Communication: Rediscovery of Psychotria species, subspecies, and varieties collected in the 1990s and new records of Antirhea benguetensis (Elmer) Valeton and Ixora longifolia Smith (Rubiaceae) in Northern Sierra Madre Natural Park, Luzon, Philipp - Rachel Biag; GRECEBIO JONATHAN D. ALEJANDRO (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Biag RD, Alejandro GJD. 2020. Short Communication: Rediscovery of Psychotria species, subspecies and varieties collected in the 1990s and new records of Antirhea benguetensis (Elmer) Valeton and Ixora longifolia Smith (Rubiaceae) in Northern Sierra Madre Natural Park, Luzon, Philippines. Biodiversitas 21: 4524-4535. Tagged as the “last great forest” for it possesses the widest remaining tropical rainforest in the island of Luzon, the Northern Sierra Madre Natural Park (NSMNP) in the province of Isabela is worth-conserving. Owing to the species richness and high levels of endemism in the said area, it was identified as a key biodiversity area for conservation and protection. After a botanical exploration in the park conducted from April to August 2019, 89 Rubiaceae species were found dominated by the genus Psychotria. These Psychotria species were then separated from other genera and were morphologically examined and eventually identified. This study, therefore, primarily aims to provide the list of Psychotria species that were collected long before, particularly in the 1990s and still exist in NSMNP continuously battling against the catastrophic activities within the forest. Eight Philippine endemic Psychotria species and varieties were recollected. As to their current conservation status following IUCN criteria, we herein propose these species, except for Psychotria pubilimba, to be treated as Data Deficient (DD) since there is lack of distributional data for these species. Additional surveys are to be conducted on the areas where these species were previously collected. In this way, information on population size and threats to the species can also be obtained. P. pubilimba is restricted to Cagayan and Isabela. Only one mature individual has been found; hence, a Narrow Endemic Species (NES). Being an NES, it was then assessed as Critically Endangered (CR) based on IUCN rules. It is also worth noting that new records of Antirhea benguetensis and Ixora longifolia species were found in the park, particularly in Divilacan, Isabela. The former has been regarded as Luzon endemic, known to be distributed only in Benguet, Ilocos Sur, Rizal, and Bataan. The latter, on the other hand, is mostly distributed in the provinces of Visayas and Mindanao, and only Masbate and Palawan for Luzon. Moreover, this flora has been recorded in other parts of the world like China, India, Myanmar, Indonesia, Malaysia, and Vietnam.